If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 = 3u + -3 Reorder the terms: -18 = -3 + 3u Solving -18 = -3 + 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. -18 + -3u = -3 + 3u + -3u Combine like terms: 3u + -3u = 0 -18 + -3u = -3 + 0 -18 + -3u = -3 Add '18' to each side of the equation. -18 + 18 + -3u = -3 + 18 Combine like terms: -18 + 18 = 0 0 + -3u = -3 + 18 -3u = -3 + 18 Combine like terms: -3 + 18 = 15 -3u = 15 Divide each side by '-3'. u = -5 Simplifying u = -5
| 5x+37=x+9 | | 6x+2(6x-9)=72 | | 7/10:21/20 | | -3x-19=x+5 | | 1-7p=1-7p | | 8x+x=54 | | -x+8=x+2 | | 114/210:21/20 | | -.4x^2+.25x-.7=0 | | 2x+-10=-10 | | 1-8x=-13+2x-8x | | 3x+2(6x+11)=157 | | 2x^2+36-2295=0 | | 5x+13=2x+4 | | 1+x=2+x | | (2w-1)(2w-1)=4(w-3)(w-3) | | (10x^3y^3-15x^2y^3-15y^2)/(5xy^2) | | b-6=-4+3b | | v=1/3(3.14)(1.5)(1.5)(h) | | 3x+3(5x+16)=174 | | 5x=2x-2 | | -m+2m+6=m+6 | | 3/4×y=6 | | 9x^2-10x=-1 | | y=1/3(9)-1 | | 4-2x=-5-5x | | 2x+5=250 | | y=1/3(3)-1 | | 5-(2x-3)=8+2x | | -13+3x=8x+8x | | -6z+6+7z=11 | | x^4-x^3-5x^2=0 |